Rancang Bangun Penilaian Hasil Belajar Anak pada PAUD Soka Indah Berbasis Website - Darsih Darsih; Alifia Puspaningrum; Munengsih Sari Bunga; Faisal Basri; Moh. Ali Fikri (IKRA-ITH ABDIMAS, 2023)
Information technology in a very fast period of time is growing rapidly making iteasier for humans to access all available information, including in the world of earlychildhood education (PAUD). Early childhood education or PAUD is the level ofeducation that a child takes before he enters elementary school or elementary school.Learning from home activities require educators to be better prepared in preparinglearning activities and force educators to utilize various technologies to facilitatelearning activities. This is one of the problems that arise in the implementation oflearning during the current pandemic. So, we need a system that can providefacilities for educators, especially in recapitulating the assessment and learningoutcomes of children. Therefore, this study proposes the implementation ofAssessment and Learning Outcomes of Children at PAUD Soka Indah. Web-Basedis a website that is used to recap the results of the assessment of early childhoodlearning outcomes. After being tested, the proposed application can be implementedproperly to support the assessment of children's learning outcomes.